Eficacia de la azitromicina asociada al rar en pacientes con periodontitis crónica. clínica dental universidad católica los ángeles de chimbote-2015 - Millones Gomez, Pablo Alejandro (2016)
The aim of this study was to evaluate the efficacy of azithromycin associated with the RAR in patients with chronic periodontitis. They involved 30 adult patients, randomized into 2 groups designated by the letters A and B of 15 members each. Each patient was evaluated periodontally before Give you the scaling and root planing and optimization hygiene techniques. Patients in group A were prescribed antibiotic treatment with azithromycin 500 mg orally every 24 hours for 3 days and group B were prescribed a placebo with the same physical characteristics of the antibiotic chosen. Patients were evaluated at 3, 4 and 5 months. Efficacy was evaluated using the Student t test to compare means, considering a level of significance for the values of p <0.05. It was found that both groups were able to improve probing depth and clinical grip level however no statistically significant differences between them, clearly demonstrated the effectiveness of scaling and root planing and periodontal therapy regardless of the use of systemic antimicrobial.